'Goalkeepers are players too': key attributes coaches' look for in talented youth soccer goalkeepers - Leago Lethole; Alliance Kubayi; Abel Toriola; Paul Larkin; Joseph A. Stone (BMC, 2024)
Abstract Objective Currently, there is a gap in knowledge on what the key goalkeeper attributes are during talent identification and selection in soccer. Hence, the objective was to investigate South African coaches' perceptions regarding key attributes of talented youth soccer goalkeepers. Design Cross-sectional survey. Methods A total of 173 soccer coaches (130 men and 43 women; M age = 36.6 ± 10.4 years; M coaching experience = 8.4 ± 7.3 years) were purposively recruited to participate in the study. All of the participants completed the Talent Identification Questionnaire in Soccer - Goalkeepers (TIDQS-GK). Results The six-component solution identified by the principal component analysis accounted for 68.96% of the total variance. Coaches deemed psychological (e.g. concentration, bravery, self-discipline), physical (e.g. speed, flexibility), social (e.g. coachability, communication), technical (e.g. catching the ball, first touch), tactical (e.g. defensive organisation against set plays) and perceptual-cognitive skills (e.g. decision-making) as important factors in identifying talented goalkeepers. Conclusions The study offers new insights into the key attributes that soccer coaches look for in talented goalkeepers such as concentration, bravery, speed, coachability and decision-making and could direct coaches towards more objective evaluation strategies for informing their decisions.